Design of Teacher Management Information System Using Design Thinking at SDN 101827 Based on Mobile - Muhamad Alda; Sasgia Sinta Putri; Tiara Arzhety Lubis; Rani jumiannisa Sinaga (STMIK Indonesia Banda Aceh, 2026)
The use of mobile technology is increasingly important for schools in improving the smoothness of teacher administration, making it faster and more accessible. At SDN 101827, various processes such as attendance recording, leave requests, and teacher data management are still carried out manually, often resulting in delays, data inaccuracies, and low efficiency. This study designed a mobile-based Teacher Management Information System (SIMAGUR) as a solution to streamline and accelerate the administrative process. The Design Thinking method was applied through five stages, starting from identifying needs, formulating problems, developing ideas, creating prototypes, and testing the system. In the testing phase, the System Usability Scale (SUS) was used to measure user perceptions of the application's ease of use. The score was calculated based on the SUS rules with a value conversion using a factor of 2.5 to obtain the final score. The test results on five respondents produced an average score of 80.00, which is classified as Excellent (B) . These findings indicate that the SIMAGUR design has a good level of usability, is easy to understand, and provides a positive experience for users. Overall, the designed system has the potential to support schools in managing teacher administration in a more organized and efficient manner.